An investigation of binding ability of Ixodes persulcatus Schulze Salp15 with Lyme disease spirochetes - Murase, Y.; Konnai, S.; Yamada, S.; Githaka, Naftaly W.; Isezaki, M.; Ito, T.; Takano, A.; Ando, S.; Kawabata, H.; Murata, S.; Ohashi, K. (Elsevier, 2015)
Salp15, a 15-kDa tick salivary gland protein, has several suppressive modes of activity against host immunity and plays a critical role in the transmission of Lyme disease spirochetes in Ixodes scapularis and Ixodes ricinus, major vectors of Lyme disease in North America and Western Europe. Salp15 adheres to Borrelia burgdorferi and specifically interacts with its outer surface protein C (OspC), protecting the spirochete from antibody-mediated cytotoxicity and facilitating infection in the mice. Recently, we identified two Salp15 homologues, IperSalp15-1 and IperSalp15-2, in Ixodes persulcatus, a vector for Lyme disease in Japan. Here we describe the function of IperSalp15 in the transmission of Lyme borreliosis. To investigate the function of IperSalp15, recombinant IperSalp15-1 and IperSalp15-2 were prepared in bacterial and insect cells. Both were identified in the sera of tick-immunized hamsters, indicating that these are secretory proteins in exposed host animals. Solid-phase overlay and indirect fluorescence assays showed that IperSalp15 binds to OspC from B. burgdorferi, Borrelia garinii, and Borrelia afzelii. Importantly, this binding likely protected the spirochete from antibody-mediated cytotoxicity in vitro. In addition, IperSalp15 tended to facilitate infection in mice. Thus, further characterization of tick molecules, including IperSalp15, could lead to the development of new strategies to prevent the transmission of tick-borne diseases.